2018
DOI: 10.1016/j.bbmt.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the Best Donor for Haploidentical Transplant: Impact of HLA, Killer Cell Immunoglobulin-Like Receptor Genotyping, and Other Clinical Variables

Abstract: The use of post-transplant cyclophosphamide (PTCy)-based haploidentical (haplo) transplant is increasing worldwide. However, because multiple potential haplo donors are usually available, data-driven guidance is clearly needed to help transplant centers prioritize donors. To that end, we retrospectively analyzed 208 consecutive donor-recipient pairs receiving PTCy-based haplo transplant at a single institution. Median recipient and donor age were 52 years (range, 19 to 75) and 38 years (range, 15 to 73), perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
107
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 58 publications
1
107
6
Order By: Relevance
“…Similarly, in haplo‐HCT with PTCy, Kasamon et al also found that greater HLA disparity did not appear to worsen overall outcomes . This has been further confirmed by a recent study by Solomon et al and other investigators from European Group for Blood and Marrow Transplantation (EBMT) . Therefore, recent retrospective studies have suggested that HLA disparity is not associated with prognosis after haplo‐HCT …”
Section: Hla Disparitymentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, in haplo‐HCT with PTCy, Kasamon et al also found that greater HLA disparity did not appear to worsen overall outcomes . This has been further confirmed by a recent study by Solomon et al and other investigators from European Group for Blood and Marrow Transplantation (EBMT) . Therefore, recent retrospective studies have suggested that HLA disparity is not associated with prognosis after haplo‐HCT …”
Section: Hla Disparitymentioning
confidence: 74%
“…However, some specific HLA loci have been shown to be associated with transplant outcomes. In haplo‐HCT using PTCy, Solomon et al suggested that HLA‐DP nonpermissive mismatch was associated with improved overall survival (OS; 71% vs 56%) and reduced relapse (16% vs 40%), whereas HLA‐DR mismatch was associated with a better OS (63% vs 47%) and reduced NRM (11% vs 46%) . In haplo‐HCT using the Beijing protocol, although the high degree of HLA allele mismatches did not adversely affect transplant outcomes in haplo‐HCT, each HLA allele mismatch had a different effect.…”
Section: Hla Disparitymentioning
confidence: 99%
“…We decided to preferentially select mothers as donors whenever possible due to a number of publications hypothesizing immunological tolerance between the mother and the fetus during pregnancy, producing a lifelong downregulation of immune responses, and thus development of tolerance, toward antigens of maternal origin . However, consistent with other previous reports, we observed no survival advantage linked to the gender of the donor parent, suggesting that neither alloreactivity encoded by the Y chromosome of the father or immunological tolerance between the mother and child plays a major role in the success of haploidentical transplantations with Post‐Cy.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Solomon et al 19 reported that neither parent demonstrated a survival advantage over the other. We decided to preferentially select mothers as donors whenever possible due to a number of publications hypothesizing immunological tolerance between the mother and the fetus during pregnancy, producing a lifelong downregulation of immune responses, and thus development of tolerance, toward antigens of maternal origin.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious next challenge for the scientific community is to understand the variables that may make haplo-HCT safer and better. Multiple studies, editorials and algorithms later, this remain an area of active research and debate (Wang et al, 2014;Handgretinger, 2014;Chang et al, 2016;Solomon et al, 2018;McCurdy et al, 2018;Bacigalupo & Laurenti, 2018).…”
mentioning
confidence: 99%